History, critique and politics: contribution to the construction of a historical materialist approach to political theory and the history of ideas - Flohr, Mikkel (Politica, 2026)
This article outlines a historical materialist approach to political theory and the history of ideas, based in the work of Karl Marx, based on the most recent advances in the field. It begins with an examination of Marx’s critique of Hegel’s Philosophy of Right and his development of a historical materialist understanding of the state, society, and, subsequently, political economy. The discussion then turns to the relevance of ideas from a historical materialist perspective, focusing on their role within and as part of historically situated social relations and institutions. Finally, the article proposes a historical materialist approach that integrates close textual analysis, contextual interpretation, and political self-reflexivity. This approach is not neutral but politically engaged and reflexive about it; it actively seeks to understand and challenge the social and material conditions that shape our ideas and collective existence.